Interdisciplinary Collaboration Between Veterinary and Communication Students to Promote Communication Skills: A Qualitative Pilot Study - Tvarijonaviciute, Asta; Roca, Delfina; Escribano, Damián; Franco-Martínez, Lorena; Bernal, Luis J.; Ceron, Jose J.; Martínez-Subiela, Silvia; Rojo-Villada, Pedro A. (Frontiers in Veterinary Science, 2020)
Interdisciplinary collaborations are increasingly gaining popularity, as are active learning and innovative learning strategies. However, relatively little research has been performed related to interdisciplinary learning methodologies in higher education. In the present work, a pilot activity between communication and veterinary students was performed, consisting in performance of mock interviews at professional television studio. Besides some drawbacks such as low participation rates by veterinary students, the activity was associated with number of benefits, including enhanced acquirement of communication skills, greater topic-related knowledge assimilation, and reinforced practical application of the theoretical concepts.